Subject and World. Ontological premises of Kantian concept of autonomy of Reason - Blanco Brotons, Francisco (Pensamiento. Revista de Investigación e Información Filosófica, 2019)
On this paper we ask ourselves about the ontology of the finite rational being in Kan’t normative theory and about the historic dynamics of «realization» that it sets in motion. With this we don’t pretend to attribute to Kant a derivation of what ought to be from what is. If we agree to call «fundamental ontology» to that universal inquiry about the sense of the being that takes root in the problematization of the subject’ being, my hypothesis is that the factum of the concience of the ought-to-be, like ratio cognoscendi of the freedom, heartens a fundamental ontology beyond the trascendental idealism. The opening of this problem in Kant’s discourse takes place with the Critique of Judgement and reveals the concept of world like a key piece in this level of intelligibility.
Keywords: Kant; freedom; autonomy; heteronomy; practical reason; practical subject; world; common sense; sociability; human nature; education; community; state; culture